The Correlation Between Weight Increment and Stunting in Children 0-24 Months - Hanna Dyahferi Anomsari; I Gusti Eka Ayu Pratiwi; Irwanto Irwanto (Humanistic Network for Science and Technology (HNST), 2020)
Globally in 2016, 22.9% or 154.8 million children under 5 years of age suffered from child stunting. The prevalence of stunting in Indonesia is 19.3% and in east java it reaches almost 30%. Negative effect of stunting cannot be repair or irreversibel, especially brain damage and the management of stunting is complex, so preventing and reducing child become stunting is more important. Analysis of growth patterns and the detection of aberrant growth patterns provide critical information for the detection of pathologic conditions. Weight-for-age is the most commonly used index of nutritional status. Weight loss, or failure to gain normally, is often the first sign of pathology. If routine weight measurements could be used to detect the risk of linear growth faltering, the role of posyandu in stunting prevention could be enhanced. Purpose of this study is to find a relationship of weight increment in 2, 3, 4, and 6 month and stunting in children aged 0-24 months. There was a significant correlation weight increment for 6 months with stunting (r= -0.432, p=0.004) Keywords: weight increment; stunting; growth interpretation